Bicarbonate-Reversible and Irreversible Inhibition of Photosystem II by Monovalent Anions - Stemler, Alan (1985)
We tested a number of inhibitory monovalent anions for their primary site of action on photosystem II(PSII) in chloroplasts. We find that the inhibitory effects of F(−), HCO(2)(−), NO(2)(−), NO(3)(−), and CH(3)CO(2)(−) are all reversed by addition of a high concentration of HCO(3)(−). This class of anions competitively inhibits H(14)CO(3)(−) binding to PSII. All of those anions tested reduced H(14)CO(3)(−) binding more in the light than in the dark. We conclude that the primary inhibitory site of action of a number of monovalent anions is at the HCO(3)(−) binding site(s) on the PSII complex. The carbonic anhydrase inhibitor gold cyanide, and also azide, inhibit PSII but at a site other than the HCO(3)(−) binding site. We suggest that the unique ability of HCO(3)(−) to reverse the effects of inhibitory anions reflects its singular ability to act as a proton donor/acceptor at the anion binding site. A similar role has been proposed for non-substrate-bound HCO(3)(−) on carbonic anhydrase by Yeagle et al. (1975 Proc Natl Acad Sci USA 72: 454-458).